Massive Fetal Transfusion During an Emergency Ex Utero Intrapartum Treatment for a Congenital Infantile Fibrosarcoma: A Case Report. Issue 7 (1st October 2019) - Oster, Andrew S.; Reina, Eduardo; Fehr, James J.; Moore, Robert P.; Cox, Thomas E.; George, Preeta
Abstract : Although originally described to assist airway management of fetal congenital malformations with life-threatening airway obstruction, the indications for an ex utero intrapartum treatment (EXIT) have expanded to include surgical resection of lesions that are potentially incompatible with life in the absence of uteroplacental circulatory support. We describe the case of an infantile fibrosarcoma (IFS) that presented with fetal hydrops and was successfully managed with an emergency EXIT that necessitated the initiation of a massive fetal blood transfusion both with and without the support of uteroplacental circulation.